New chloramphenicol Schiff base ligands for the titanium-mediated asymmetric aldol reaction of α, β-unsaturated aldehydes with diketene: a short synthesis of atorvastatin calcium. Issue 79 (9th August 2016) - Wang, Haifeng; Yan, Linjie; Xiong, Fangjun; Wu, Yan; Chen, Fener
Abstract : Several novel chiral Schiff base ligands were prepared from a commercially available chloramphenicol base and applied to the titanium-mediated asymmetric aldol reaction of diketene with various α, β-unsaturated aldehydes. Abstract : Several novel chiral Schiff base ligands were prepared from a commercially available chloramphenicol base and applied to the titanium-mediated asymmetric aldol reaction of diketene with various α, β-unsaturated aldehydes. This reaction proceeded in good yield with high enantioselectivity. The synthetic utility of this methodology was demonstrated in the short synthesis of atorvastatin calcium.